Porosity and Inclusion Detection in CFRP by Infrared Thermography. (19th November 2012) - Toscano, C.; Meola, C.; Iorio, M. C.; Carlomagno, G. M.
Abstract : The ever wide use of composite materials in the aeronautical industry has evidenced the need for development of ever more effective nondestructive evaluation methodologies in order to reduce rejected parts and to optimize production costs. Infrared thermography has been recently enclosed amongst the standardized non destructive testing techniques, but its usefulness needs still complete assessment since it can be employed in several different arrangements and for many purposes. In this work, the possibility to detect slag inclusions and porosity is analyzed with both lock-in themography and pulse thermography in the transmission mode. To this end, carbon-fiber-peinforced polymers different specimens are specifically fabricated of several different stacking sequences and with embedded slag inclusions and porosity percentages. As main results, both of the techniques are found definitely able to reveal the presence of the defects above mentioned. Moreover, these techniques could be considered complementary in order to better characterize the nature of the detected defects.